Sevelamer Attenuates Bioprosthetic Heart Valve Calcification - Meng, Zhen; Li, Zhe; Zhang, Erli; Zhang, Li; Liu, Qingrong; Wu, Yongjian (Frontiers in Cardiovascular Medicine, 2021)
Objective: Sevelamer hydrochloride is a phosphate binder used to treat hyperphosphatemia in chronic kidney disease (CKD) patients that can reduce valvular and vascular calcification. The aim of this study was to examine the effects of sevelamer treatment on calcification in bioprosthetic heart valves (BHVs). Methods: Wister rats were randomly divided into three groups according to sevelamer intake and implantation (sham–sham operation; implant–implantation and normal diet, implant+S implantation, and sevelamer diet). Two kinds of BHVs—bovine pericardium treated with glutaraldehyde (GLUT) or non-GLUT techniques—were implanted in rat dorsal subcutis at 4 weeks. After implantation, sevelamer was administered to the implant+S group. The animals were executed at days 0 (immediately after implantation), 7, 14, 28, and 56. Calcium levels were determined by atomic absorption spectroscopy and von Kossa staining. Serum biochemistry analysis, Western blotting, real-time quantitative polymerase chain reaction, alkaline phosphatase activity measurement, histopathologic analysis, immunohistochemistry, and enzyme-linked immunosorbent assay were conducted to identify the anti-calcification mechanism of sevelamer. Results: Non-GLUT crosslinking attenuates BHV calcification. Serum phosphate and calcium remained unreactive to sevelamer after a 14-day treatment. However, the mean calcium level in the implant+S group was significantly decreased after 56 days. In addition, the PTH level, inflammatory cell infiltration, system and local inflammation, and expression of Bmp2, Runx2, Alp, IL-1β, IL-6, and TNF-α were significantly reduced in the implant+S group. Conclusion: Sevelamer treatment significantly attenuated the calcification of BHVs and had anti-inflammation effects that were independent from serum calcium and phosphate regulation. Thus, sevelamer treatment might be helpful to improve the longevity of BHVs.